The brain and spinal cord - AIMS Multimedia (Chatsworth, CA : AIMS Multimedia, 1997)
AIMS Multimedia's back to basis is a CD-ROM series designed specifically for the classroom. This CD-ROM program contains complete linear video, interactive quiz with video reinforcement, bulletin board, glossary, test with record keeping and teaching management systems
System requirements : Macintosh ; Drag folder to your hard drive then double clickl on the program icon
System requirements : Windows ; Run' install.exe' from cd-rom.Double click on the program icon.
Keywords: Brain; Spinal Cord